2014
DOI: 10.1590/s0080-623420140000400009
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care mapping for patients at risk of falls in the Nursing Interventions Classification

Abstract: Objetivo: Identificar los cuidados de enfermería prescritos para pacientes hospitalizados con riesgos de caídas y compararlos con las intervenciones de la Nursing Interventions Classifications (NIC). Método: Estudio transversal realizado en un hospital universitario del sur de Brasil. La recolección de datos fue retrospectiva en un sistema informatizado de registros de enfermería. La muestra se constituyó por 174 pacientes adultos internados en unidades clínicas y quirúrgicas con el Diagnóstico de Enfermería R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
0
13
0
15
Order By: Relevance
“…Therefore, the socialization enhancement and cognitive stimulation are also important to improve the elderly quality of life (Dunlop et al. ; Gobbens et al., ; Heuberger & Wong, ; Hickman et al., ; Luzia, Almeida, & Lucena, ; Luzia, Victor, & Lucena, ; McDaniel, Kemmner, & Rusnak, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the socialization enhancement and cognitive stimulation are also important to improve the elderly quality of life (Dunlop et al. ; Gobbens et al., ; Heuberger & Wong, ; Hickman et al., ; Luzia, Almeida, & Lucena, ; Luzia, Victor, & Lucena, ; McDaniel, Kemmner, & Rusnak, ).…”
Section: Discussionmentioning
confidence: 99%
“…English/Portuguese J Nurs UFPE on line., Recife, 11(12):5066-73, Dec., 2017 5069 2017 The fear of falling has been reported in many articles and brings to the elderly, especially the elderly with the risk of falls, disabling feelings and social exclusion. A study found that the frequency of fear of falling reached almost all the elderly subjects submitted to the tests.…”
Section: Methodsmentioning
confidence: 99%
“…For patients on the MC unit, the most frequently documented outcome was Tissue Integrity: Skin and Mucous Membranes (1101). In another study, the authors observed the linkage of this outcome to the diagnosis Impaired Tissue Integrity (00044) on a MC unit (Luzia, Almeida, & Lucena, 2014). The linkages of this nursing diagnosis with outcomes and interventions describe the different needs for professional practice in both units in this study.…”
Section: Discussionmentioning
confidence: 62%